Dr Mamoru Kawaguchi: His grand thought, prominent works, and contribution to the advancement of spatial structures. Issue 1 (March 2020) - Kato, Shiro
This article describes an engineer, his grand thought, prominent works, and contribution to the advancement of spatial structures based on geometry and mechanism. He is Dr Mamoru Kawaguchi, who lived in Japan for almost 90 years from 1932 to 2019. In his life, he designed a large number of epoch-making structures in the field of spatial structures in Japan and worldwide. These encompass structures of wood, concrete, steel, fabrics, and even air and water. His approach for structural design is very strict and broad with respect to geometry and mechanism and with respect to design concept, analysis, construction, fail-safe, and control as same as an academician of philosophy. The structures of Yoyogi Swimming Pool for the Tokyo Olympic Games 1964, the Grand Roof of the Osaka World Exhibition 1970, Fuji Group Pavilion, Pantadome, Suspendome, and a jumbo fabric carp flying across the sky are introduced in this article in order to remember him and to highlight his grand thought and eminent spatial structures.